Understanding the Removal of Classroom Auditory Distractors: An Interactive Design - Smith, Gregory W.; Classen, Audra I.; Riccomini, Paul J.; Brewer, Robyn R. (Journal of the American Academy of Special Education Professionals, 2018)
Students with a specific learning disability (SLD) have unique learning needs that must be met. Thus, it is imperative for teachers to incorporate flexible instructional materials, techniques, and strategies for academic progress to take place. One way teachers can be flexible is by allowing students with disabilities to take standardized (i.e. high stakes tests) in removed, quieter settings rather than the typical classroom. Therefore, this naturalistic inquiry study sought to understand what happens when noise reducing headphones were introduced to students, specifically those with SLD, in an elementary classroom. Student descriptions and perceptions of wearing headphones during a reading comprehension assessment indicated student participants seemed to enjoy the experience. Student explanations for this response focused on three principles: (a) internal (i.e. to help the individual internally), (b) external (i.e. to reduce external distraction), and (c) internal and external (i.e. to help the individual internally by reducing external distraction).